A potential role of a special type of abortive seeds in Cunninghamia lanceolata: promoting the growth of healthy seedlings in active aluminum ions-rich soil - Mu, Shi-Yan; Yang, Ya-Ting; Qu, Xiao-Yu; Wang, Fang-Fang; Ma, Fang-Fang; Ding, Zhen-Ning; Ye, Ling-Peng; Zhang, Ya-Ling; Zhang, Jia-Jun; Lyu, Meng-Meng; Li, Shu-Bin; Cao, Guang-Qiu; et al. (Frontiers in Plant Science, 2024)
Background and aims: "Astringent seed" is a type of abortive seed frequently observed in Chinese fir (Cunninghamia lanceolata). It is widely recognized but poorly understood for its underlying causes.This study investigates the potential of astringent seeds to alleviate the toxic effects of active aluminum ions.Methods: This study involved treating seeds and seedlings with two distinct concentrations of astringent seeds water extracts under the aluminum ion stress. Then the germination of seeds and growth of seedlings were evaluated and compared.Results: Under aluminum stress, both seed germination and seedling growth were notably inhibited.Treatment with a low-concentration of the extract significantly alleviated this inhibition. Root elongation in the seedlings increased by 36.95% compared to the control group, and the aluminum ion accumulation at the root tips was reduced by 38.89% relative to the aluminum-stressed group. This treatment also normalized the levels of malondialdehyde (MDA) in the roots and leaves, enhanced the activities of antioxidative enzymes such as superoxide dismutase (SOD) and catalase (CAT), and restored the levels of endogenous hormones including gibberellin (GA3), indole-3-acetic acid (IAA), methyl jasmonate (Ja-ME), and abscisic acid (ABA). Furthermore, the low-concentration of the extract positively impacted the disorganized chloroplast structures. In contrast, a high-concentration of the extract failed to revert most of these stress indicators.Low concentrations of astringent seed water extract effectively alleviate the inhibitory effects of aluminum ions on seed and seedling. This implies that in natural environments, the proximity of healthy seeds to astringent seeds could potentially enhance their growth.